2020
DOI: 10.1074/mcp.tir119.001820
|View full text |Cite|
|
Sign up to set email alerts
|

Concentration Determination of >200 Proteins in Dried Blood Spots for Biomarker Discovery and Validation

Abstract: The use of protein biomarkers as surrogates for clinical endpoints requires extensive multilevel validation including development of robust and sensitive assays for precise measurement of protein concentration. Multiple reaction monitoring (MRM) is a well-established mass-spectrometric method that can be used for reproducible protein-concentration measurements in biological specimens collected via microsampling. The dried blood spot (DBS) microsampling technique can be performed non-invasively without the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…By focussing the mass spectrometer, the analysis gains sensitivity and, in contrast to shotgun-based discovery methods, enables the observation of the analytes in every sample. Therefore, targeted methods are particularly well suited for measuring larger cohorts and clinical applications [8,14].…”
Section: Discovery and Targeted Proteomics -Two Sides Of The Same Coinmentioning
confidence: 99%
“…By focussing the mass spectrometer, the analysis gains sensitivity and, in contrast to shotgun-based discovery methods, enables the observation of the analytes in every sample. Therefore, targeted methods are particularly well suited for measuring larger cohorts and clinical applications [8,14].…”
Section: Discovery and Targeted Proteomics -Two Sides Of The Same Coinmentioning
confidence: 99%
“…Targeted MS methods have been developed, again especially where interferences obfuscate immunoassays 128 or where additional biological context is required 129 . Likewise, volumetric absorptive micro-sampling VAMS blood collection devices (e.g., Mitra devices or dried blood spots) allow patients to mail samples from home to analytical labs to undertake SRM/MRM/PRM assays quantifying CVD risk-associated apolipoproteins 130 or other markers 131 . In summary, consumer-based CVD proteomics-based precision medicine testing services are now coming of age.…”
Section: Translating Proteomics To Precision Medicinementioning
confidence: 99%
“…Previous studies [7,[12][13][14] have demonstrated the possibility of characterizing protein abundance levels from DBS, both for fewer analytes in large sample sets and for a higher number of proteins from smaller samples sets constructed under laboratory conditions. The recent work by Eshghi and colleagues [12] reports encouraging results: absolute concentrations were determined for over 200 proteins by mass spectrometry. In that study, 50 µL of blood drawn using finger prick technique was pipetted onto spots of the same type of paper cards used here and then five 6 mm punches (one from each spot) was used for analysis.…”
Section: Dbs Offers Flexibility and Convenience In Sampling And Handlingmentioning
confidence: 99%